The Value of Precontract Information About an Agent's Ability in the Presence of Moral Hazard and Adverse Selection - BANKER, RAJIV D.; DARROUGH, MASAKO; LI, SHAOPENG; THREINEN, LUCAS (Journal of Accounting Research, 2019)
ABSTRACT We analyze the expected value of information about an agent's type in the presence of moral hazard and adverse selection. Information about the agent's type enables the principal to sort/screen agents of different types. The value of the information decreases in the variability of output and the agent's risk aversion, two factors that are typically associated with the severity of the moral hazard problem. However, the value of the information about agent type first increases but ultimately decreases in the severity of adverse selection. The decrease comes about because the means available to the principal to induce effort—namely, the pay–performance sensitivity—must also be used to sort/screen agents, and these two goals conflict. This decline in value occurs despite the monotonically increasing importance of the information in determining the principal's expected profits. Further, we show that the peak value of information occurs at a predictable level of adverse selection. These results imply that over some range, the importance of the information will be increasing, and the value of the information will be simultaneously decreasing, in the severity of adverse selection.